Pore Size Distribution of Unsupported SnO2 Membranes Prepared by Sol-Gel Process - Souza Brito, Giancarlo Esposito de [UNESP] (1994)
Unsupported SnO2 membranes were prepared by sol-gel process and characterized by N-2 adsorption-desorption isotherms and X-ray diffraction. Results show that the texture of dried samples does not change appreciably with the concentration of electrolyte. All of the pore size range used in ultrafiltration process was screened using sintering temperature between 300 and 700 degrees C.